Normality Test of NEPSE Sensitive Index - Vaidya, Rashesh; Sharma, Dilli Raj; Dangol, Jitendra (Madhyabindu Journal, 2023)
A return from the stock market is assumed to follow the random walk hypothesis. An investor is concerned about the risk and returns of the fund in which he or, she has invested. A risk-averse investor develops a portfolio with a secured return followed with a perfect prediction. Hence, a normality test for the market return is an easier way to diversify and eliminate risk. Thus, this paper tests the normality of the returns from the ‘blue-chip’ stocks in the context of NEPSE. A NEPSE Sensitive Index is an index calculated based on the trade of stocks for large, capital-based Nepalese listed companies with better earning histories and higher book values. The NEPSE sensitive index and NEPSE sensitive float index are tested for normality. The paper followed the data visualization technique, descriptive statistics, and test statistics to test the normality and find out the parameters of normal distribution. The paper found that the daily return from both indices best fit a normal distribution. Hence, two basic statistical parameters from the returns, i.e., the mean and standard deviation, are sufficient to estimate future trend for ‘blue-chip’ stock return in Nepal. The governing body should develop a new index that would better represent the market movement in the coming days that would be beneficial to predict the return movement from NEPSE.